O‘SMIR FUTBOLCHILAR FAOLIYATIDA CHIDAMLILIK VA IRODA KUCHINI RIVOJLANTIRISH - Xaitov, A.U. (SCIENCE and SOCIETY, 2024)
The article examines the factors of obstacles and difficulties in the activities of teenage football players. An experiment was conducted to increase the resilience of teenage football players to obstacles and difficulties that arise in their careers, as well as to increase willpower in overcoming them. According to the results of the experiment, teenage football players increased endurance and willpower.
Keywords: teenager; football; barrier factor; volitional qualities; endurance; strength of will